Perovskite Materials, Devices and Integration (IntechOpen, 2021)
Perovskites have attracted great attention in the fields of energy storage, pollutant degradation as well as optoelectronic devices due to their excellent properties. This kind of material can be divided into two categories; inorganic perovskite represented by perovskite oxide and organic-inorganic hybrid perovskite, which have described the recent advancement separately in terms of catalysis and photoelectron applications. This book systematically illustrates the crystal structures, physic-chemical properties, fabrication process, and perovskite-related devices. In a word, perovskite has broad application prospects. However, the current challenges cannot be ignored, such as toxicity and stability.